LaneConnex: An Integrated Biomedical Digital Library Interface - Debra S. Ketchell; Ryan Max Steinberg; Charles Yates; Heidi A. Heilemann (Information Technology and Libraries, 2009)
This paper describes one approach to creating a search application that unlocks heterogeneous content stores and incorporates integrative functionality of Web search engines. LaneConnex is a search interface that identifies journals, books, databases, calculators, bioinformatics tools, help information, and search hits from more than three hundred full-text heterogeneous clinical and bioresearch sources. The user interface is a simple query box. Results are ranked by relevance with options for filtering by content type or expanding to the next most likely set. The system is built using component-oriented programming design. The underlying architecture is built on Apache Cocoon, Java Servlets, XML/XSLT, SQL, and JavaScript. The system has proven reliable in production, reduced user time spent finding information on the site, and maximized the institutional investment in licensed resources.